2017
DOI: 10.1590/0034-7167-2016-0611
|View full text |Cite
|
Sign up to set email alerts
|

Deaths among the elderly with ICU infections

Abstract: Objective: to evaluate the clinical outcome of elderly patients admitted to intensive care units who had nosocomial infection, correlating the fi ndings with sociodemographic and clinical variables. Method: descriptive research, performed with 308 elderly patients. The collection was made from medical records and covers the years 2012 to 2015. Uni-/bivariate analyses were performed. Results: a statistical association was found between the clinical outcome types and the variables age, length of stay, presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 27 publications
0
14
0
9
Order By: Relevance
“…Furthermore, elderly inpatients with HAIs have poor prognosis and increased economic burden [18]. One study evaluated elderly patients who had an HAI in the ICU and found that clinical outcomes of the elderly who acquired an infection in the ICU were influenced by sociodemographic and clinical variables that increase mortality rates [19]. Another study of HAI in elderly patients identified the following risk factors: advanced age; comorbid neurological and chronic noncommunicable diseases such as cerebral hemorrhage, cerebral infarction, brain neoplasms, diabetes mellitus, coronary artery disease, malignant tumor and malignant hematonosis; hospital days before HAI; ICU admission; and device use [9].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, elderly inpatients with HAIs have poor prognosis and increased economic burden [18]. One study evaluated elderly patients who had an HAI in the ICU and found that clinical outcomes of the elderly who acquired an infection in the ICU were influenced by sociodemographic and clinical variables that increase mortality rates [19]. Another study of HAI in elderly patients identified the following risk factors: advanced age; comorbid neurological and chronic noncommunicable diseases such as cerebral hemorrhage, cerebral infarction, brain neoplasms, diabetes mellitus, coronary artery disease, malignant tumor and malignant hematonosis; hospital days before HAI; ICU admission; and device use [9].…”
Section: Discussionmentioning
confidence: 99%
“…This state of dependence, whether due to the appearance of non-transmissible chronic diseases and their consequences or due to the cognitive and functional losses of advancing age demand home care and changes in the daily lives of many families. (1)(2)(3)(4) The family is assigned the responsibility of assisting its aging members. The family caregivers are part of the informal support network, consisting of family members, friends, acquaintances, and neighbors, who work without pay.…”
Section: Introductionmentioning
confidence: 99%
“…This fact marks the difference from the formal network of caregivers, composed of professionals, whether at home, in hospital or outpatient institutions. (2) Informal care is the most frequent model of care for the elderly identified in the literature, but there is no clear description of the geographical areas where this care takes place. (3) Many relatives prefer this, possibly because of their cultural values, lack of formal care services or lack of financial resources to hire a caregiver.…”
Section: Introductionmentioning
confidence: 99%
“…The process of ageing population occurs through the constant increase of the years of life associated with the drop in fertility and mortality, and can be defined as a multifaceted process throughout the entire life course (1)(2) .…”
Section: Introductionmentioning
confidence: 99%